The Use of E-Comics Based on A Realistic Mathematical Approach to Improve Critical and Creative Thinking Skills of Elementary School Students - Siti Yulaichah; Neni Mariana; Wiryanto Wiryanto (IJORER : International Journal of Recent Educational Research, 2024)
Objective: In the 21st century, critical and creative thinking skills must be nurtured and grown from elementary school. The way to improve this ability can be done by utilizing Mathematics subjects but with a realistic approach that allows students to immediately learn critically and creatively according to the context of everyday life so that students can think organized and creatively in their lives, not limited to subjects. One way to facilitate the learning objectives of Mathematics with a Realistic Approach is to utilize e-comic learning media that allows students to see the context of the lesson using their visual abilities. Method: This research uses literature studies by searching relevant journals, books, and articles using the Publish or Perish application. Results: The study showed that e-comics improved students' critical thinking skills and creativity. In addition, researchers also found that several factors make mathematics learning with a realistic approach that utilizes e-comics efficient, as well as steps to conduct mathematics learning with a realistic approach that utilizes e-comic learning media. Novelty: This research uses an innovative and creative approach to improving students' critical and creative thinking skills through Mathematics learning using e-comic learning media.